"Scary and Effective, Definitely Pushes Me to Quit Smoking": Developing Waterpipe Pictorial Health Warnings Targeting Young Adults in Lebanon. Issue 9 (23rd February 2022) - Asfar, Taghrid; Chehab, Sara; Schmidt, Michael; Ward, Kenneth D; Maziak, Wasim; Nakkash, Rima
Abstract: Introduction: Waterpipe (WP) smoking is the leading tobacco use method among young adults in Lebanon. WP use is harmful, yet misperceptions about its safety exist. Implementing pictorial health warning labels (HWLs) on WP products is a promising strategy to correct this misperception. This study aimed to culturally adapt a set of 12 pictorial HWLs recently developed by an international expert panel to young adults in Lebanon. HWLs were grouped into four themes: WP health risks, WP harm to others, WP-specific harms, and WP harm compared to cigarettes. Aims and Methods: We conducted nine focus groups among WP smokers and nonsmokers ( N  = 77; 52% females; age 18–34 years) to explore participants' perceptions of the developed HWLs on attention, reaction (fear, avoidance), effectiveness (harm perception), and improvement (design/content, relatedness). Sessions were audio-taped, transcribed verbatim, and analyzed using directed qualitative content analysis. Results: Emotionally provocative warnings were perceived as most effective, while symbolic and abstract warnings were found not believable. Warnings depicting visible bodily health effects and harm to babies seemed most promising. Participants were generally skeptical about Theme 4 because it might encourage switching to cigarettes. For cultural adaptation, participants recommended using shorter text with affirmative phrases, increasing the picture's size and improving their quality, adding the WP device picture to enhance HWLs' relatability, and develop testimonial messages that depict real people and stories. Conclusions: Results will provide Lebanon and perhaps other countries in the Eastern Mediterranean Region with evidence-based HWLs that they can further develop, test, and implement within their specific culture. Implications: Results provide Lebanon with evidence-based WP-specific pictorial HWLs that can be further developed and tested. HWLs provoking negative affect, with visible health consequences, and depicting harm to babies are promising. Participants recommended using definitive scientific claims presenting the health risks in numerical form. However, this needs to be balanced against protecting the credibility of HWLs scientifically and legally. Increasing the HWLs size and adding the WP device picture to the HWLs can enhance their relatability. Further research can help address some questions raised by this study, such as the potential of testimonial warnings that depict real people.